Political power and social theory. Vol. 18 - Davis, Diane E., 1953- (Amsterdam ; Oxford : Elsevier JAI, 2006)
Volume 18 of the popular "Political Power and Social Theory" series is broken up into three parts examining political power, state formation, and economic development with examples from Africa, Russia, and Chile. It also looks at the status of opposition politics in America. It is suitable for graduate students and researchers in the field of political science and social theory. Part I examines political power, state formation, and economic development with examples from Africa, Russia, and Chile. Part II looks at the history and current status of opposition politics in America. Part III discusses scholarly controversy within the discipline with some of the field's leading thinkers authoring chapters. With its international scope, this volume is a valuable reference for graduate students and researchers in the field of political science and social theory.
Description based on print version record.
Keywords: Power (Social sciences); Political sociology; Social sciences -- Philosophy; Social theory; Political science & theory; Political Science -- General